IN VITRO STUDY ON ANTIBIOTIC SUSCEPTIBILITY PATTERN OF BIOFILM PRODUCING UROPATHOGENIC ESCHERICHIA COLI ISOLATES AND THEIR MOLECULAR CHARACTERIZATION - Poovendran, Ponnusamy; Ramanathan, Nagappan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Urinary tract infection (UTI) is among the most common infectious diseases of humans in developed countries. Approximately 150 million cases are reported every year. UTI's caused in particular by biofilm producing Escherichia coli strains are related to recurrence of infections and the treatment is quite difficult. The present study is undertaken to determine the antibiotic susceptibility pattern of biofilm producing Uropathogenic Escherichia coli (UPEC) and molecular characterization by 16S rRNA sequencing. Methods: The present study comprised of 478 urine samples collected from Raja Muthiah Medical College and Hospital (RMMCH) at Chidambaram, India. All the samples were processed by standard microbiological methods and E.coli was confirmed by 16S rRNA analysis. E. coli isolates were screened for biofilm formation using Tube Method (TM), Congo Red Agar (CRA) and Tissue Culture Plate method (TCP). Subsequently, the antibiotic susceptibility test was performed using 14 different antibiotics and Minimum Inhibitory Concentration (MIC) and Minimum Biofilm Eradicate Concentration (MBEC) was determined by microtiter broth dilution method was done. Confocal Laser Scanning Microscopy (CLSM) was conducted for biofilm structured analysis. Results: Out of 478 urine sample processed, 324 (79.80 %) were found to be E. coli isolates, with respect to biofilm formation of TCP method classified the isolates as highly positive 40 (12.34%), moderate positive 152 (46.91%), and weakly positive 132 (40.74%). Among the antibiotics tested 56% and 51% of UPEC isolates were sensitive to levofloxacin and imipenem respectively. The MIC values (3-6 Î¼g/ml; 6-25 Î¼g/ml) and MBEC values (24-48 Î¼g/ml; 48-200 Î¼g/ml) were obtained for levofloxacin and norfloxacin against biofilm producing UPEC. Conclusions: Among all the antibiotics tested, the present result shows imipenem and levofloxacin were found to be very effective against biofilm producing UPEC. Key words: Â Urinary tract Infection (UTI), Uropathogenic Escherichia coli (UPEC), Biofilm, MIC, MBEC, Antibiotic resistance